Use of Subharmonics of Base Frequencies in the CSRMT Method with Loop Sources - Alexander K. Saraev; Nikita Yu. Bobrov; Arseny A. Shlykov (J, 2023)
In the controlled source radiomagnetotelluric (CSRMT) sounding method, a horizontal magnetic dipole, HMD (vertical loop) or a horizontal electric dipole, and HED (grounded line) are used as sources. When working with HMD, the source is usually tuned to resonance to increase the current in the loop. However, the disadvantage of this approach is the narrow frequency range realized in the CSRMT method (1–12 kHz) and the short operating distance from the source (600–800 m). The need to tune the source to resonance at each selected frequency reduces the efficiency of the survey. In the case of using HED for sounding, measurements are performed in a wider frequency range of 1 to 1000 kHz, and along with the signal of the base frequency, its subharmonics are measured. In this case, emitted signal measurements are possible at a distance of up to 3–4 km from the source. At the same time, the disadvantage of using HED is that it requires grounding, the arrangement of which requires additional time when working on frozen ground or dry stony soil. We consider the possibilities of generation and registration of signals of subharmonics of base frequencies when applying the CSRMT method with loop sources—HMD and VMD (horizontal loop). A matching unit (MU) based on a step-up transformer was developed, which increases the output voltage of the CSRMT transmitter. In a field test with base frequencies of 20, 40, and 80 kHz, the signal amplitudes increased by a factor of two to four for subharmonics at frequencies of 60–200 kHz and by up to 10–13 times for subharmonics at frequencies of 200–500 kHz due to transformation of signal spectrum provided by MU. The possibility of using odd subharmonics of base frequencies for inversion has been demonstrated in the results of field experiments with different sources (HED, HMD, and VMD). This expands the frequency range of the method when working with loop sources and increases the survey’s effectiveness. The use of loop sources in the CSRMT method is especially advantageous for winter work in Arctic regions.